Altering the course of schizophrenia: progress and perspectives - Millan, Mark J.; Andrieux, Annie; Bartzokis, George; Cadenhead, Kristin; Dazzan, Paola; Fusar-Poli, Paolo; Gallinat, Jürgen; Giedd, Jay; Grayson, Dennis R.; Heinrichs, Markus; Kahn, René; Krebs, Marie-Odile; et al. (Nature reviews. Drug discovery, 2016)
Schizophrenia is a debilitating and chronic disorder that is accompanied by psychosis and a broad spectrum of behavioural, cognitive and social deficits. It usually strikes in young adulthood. Currently, treatment is exclusively symptomatic, and medication has no direct, lasting influence on causal pathophysiology.Improved knowledge of the developmental anomalies provoked by genetic, epigenetic and environmental triggers of schizophrenia has fostered interest in potential 'disease-modifying' strategies for either slowing its progression or preventing its appearance in vulnerable young adults.Although awaiting further confirmation, clinical studies of pharmacotherapeutic and psychosocial and/or cognitive-behavioural interventions in young, high-risk individuals seeking help have collectively yielded evidence for a reduction in the transition to psychosis.Nonetheless, only a third or so of clinically high-risk individuals convert, so it is important to improve the prediction of transition at the level of individuals by the use of biomarkers. Multi-modal approaches combining, for example, circulating biomarkers, sensory/cognitive deficits and brain imaging hold particular promise.Although animal models for schizophrenia have limitations, diverse pharmacological treatments applied during adolescence preclude the appearance of a schizophrenia-like phenotype in adult rodents.Studies exploiting these in vivo models, as well as novel cellular paradigms such as human induced pluripotent stem cells, are refining our understanding of the cellular substrates leading to schizophrenia, and hence unveiling potentially novel targets for medication.In conclusion, though much work still remains to be undertaken, recent progress is raising the hope that it may eventually be possible to interrupt the course of schizophrenia, as well as other disorders characterized by psychosis. Of particular interest would be hybrid strategies that both relieve distress in young, at-risk individuals and reduce their conversion.
Gesehen am 28.01.2021